Behavior of RC Beams Strengthened with Galvanized Steel Mesh Using U-Wraps and Splay Anchors - Selim, Ahmed Hazem (2023)
A Master of Science thesis in Civil Engineering by Ahmed Hazem Selim entitled, “Behavior of RC Beams Strengthened with Galvanized Steel Mesh Using U-Wraps and Splay Anchors”, submitted in June 2023. Thesis advisor is Dr. Jamal Abdalla and thesis co-advisor is Dr. Rami Hawileh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).